Perbedaan Keefektifan Model Pembelajaran Experiential. Learning. Sinektik dan Pengajaran Langsung dalam Pembelajaraan Apresiasi Prosa Fiksi ditanjau dari Kecerdasan Emosional Siswa - Suharto, V. Teguh (Jurnal Pendidikan, 2011)
The goals of research were (1) to findings the difference between the studentsâ appreciation of prose fiction ability taught by experiential learning, synectic, and direct instruction learning model, (2) to findings the difference of prose fiction ability for students who have high and low emotional quotient, (3) to findings an interaction between the use of learning model and emotional quotient affecting prose fiction appreciation.The research applies quasi experimental method and 3 x 2 factorial research design. The technique of collecting data made use questionnaires for measuring studentsâ emotional quotient and test for measuring the prose fiction ability. Validity test consists of content validity, surface validity, and empirical test for searching distinction value, the grade of exercise difficulties, and the reliability. For the questionnaires, empirical wasapplied to recognize the validity and reliability.The normality test used the method of Kolmogrov-Smirnov. The homogenitytest used the method of Leveneâs test of equality of error variances. Data analysis uses Anava factor two by SPSS computer program. The inferential analysis revealedthe conclusion as follows: (1) There is a difference in those students who have been taught by experiential learning, synectic, and behavioristic learning model. The studentsâ average ability in appreciating prose fiction taught by experiential learning model is higher than those taught by synectic learning model. The studentsâ ability of prose fiction appreciation taught by synectic learning model is higher than those taught by behavioristic learning model. (2) There is a significant difference in studentsâ ability in appreciating prose fiction. The students who have high emotional quotient are able to appreciate prose fiction better than those who have low emotional quotient. The ability of prose fiction appreciation belongs to high emotional quotient students is higher than those who have less.Â (3) There is an interaction between the use of learning model and emotional quotient in affecting studentsâ appreciation of prose fiction ability.Â Kata Kunci: Komparasi Experiential Learning, Sinektik, Pengajaran Langsung, Kecerdasan Emosional, dan Kemampuan Apresiasi Prosa Fiksi